Risk Factors Associated with Ectopic Pregnancy - Jónathan Hernández Núñez; Magel Valdés Yong; Andrés Oscar Torres Chávez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2013)
Background: ectopic pregnancy has doubled in most industrialized countries and it is a major cause of maternal death. Objective: to identify risk factors predisposing to ectopic pregnancy. Methods: a case-control study was conducted in a universe of 132 patients from the municipality of Eastern Havana, operated on for ectopic pregnancy at the Dr. Luís Díaz Soto Hospital from 2009 to 2011. A random sample of 66 patients was selected to compose the study group; there was other control group with the same number of patients who didn't undergo surgery for ectopic pregnancy in this period. Variables analyzed were related to sociodemographic, obstetric and gynecological and surgical risk factors, as well as sexual behavior and smoking. The mean, standard deviation, percentage, Student's t test, chi-square statistic and odds ratio were used. Results: ectopic pregnancy was more common in white women aged 25 to 34 years; history of pelvic inflammatory disease, endometriosis, three or more induced abortions, infertility, previous ectopic pregnancy, early onset of sexual intercourse, multiple sexual partners and use of intrauterine devices were predisposing factors for ectopic pregnancy; unlike the education level, occupation, amount of deliveries, appendectomy and prior tubal surgery, or smoking. Conclusions: there are multiple risk factors leading to ectopic pregnancy and contributing to increased maternal morbidity and mortality; many of them can be modified in the primary health care.